The effect of cooperative learning model TGT-type assisted by crossword puzzle media on biology concept mastering - Dimas Adi Pratama; Kusmiyati; Tri Ayu Lestari; Muhlis (Jurnal Pijar Mipa, 2023)
This study aims to determine the effect of the cooperative learning model of the Teams Games Tournament (TGT) type assisted by crossword puzzle media on the mastery of biological concepts in class X students at SMAN 3 Kota Bima. This study used a quasi-experimental research method with a nonequivalent control group design (pretest and posttest). The population in this study were students of class X, consisting of class X 1 to X 4. The sampling technique used purposive sampling. The samples used were students of class X 3 as the control class and class X 4 as the experimental class. Data collection techniques using test instruments in the form of multiple-choice questions. The analysis technique used is the t-test with a significance level of 5% with the help of SPSS 25 for Windows. The t-test results show that the value of (2.347 > 2.010). Based on these results, it can be interpreted that the cooperative learning model of the TGT type assisted by crossword media affects the mastery of biology concepts in class X students at SMAN 3 Kota Bima.